Reactions of the students to integral volume problems and socio-psycho-mathematical relationship - (:unkn) unknown (E D P SCIENCES, 2016)
In this research; how the changes in reactions which university students give integral volume problems before solution and after solution affect the solution processes is inspected. In the study adopting qualitative paradigm's interpretive approach, case study is used as study design. Participants of the research are the 142 students which had been chosen from four different faculties of two universities in Istanbul, using nonprobability sampling. Semi-structured interviews were conducted with two students randomly chosen from every department and Integral Volume Pre Solution Test and Integral Volume Solution and After Solution Test were used as data collection tools. The data have been analyzed using descriptive analysis and presented by frequency and percentage tables. As a result of the research, it is concluded that the reactions of the students in the faculty, their familiarity to the mathematical statement and their attitude towards the problem and faculty based institutional differences such as professors, professional expectation causes the evolution of the socio-psycho-mathematical relationship between university students and problems and that affects the solution processes.
Keywords: INSTRUCTION; COMMUNITY; TEACHERS